تصميم بنية جديدة لمادة سالبة السماحية الكهربائية والنفاذية المغناطيسية Meta-Material باستخدام التوزع التجزيئي لرنانات الحلقة المشطورة - صالح, السموءل; عراج, فائق; الشيخ حسن, سامر (Latakia University Journal -Engineering Sciences Series, 2018)
A growing interest in the research results concerning the interaction of electromagnetic waves with fabricated structures that give negative electric permittivity (Ɛ) and magnetic permeability (µ) has been observed in the past few years. i.e. they acquire their electromagnetic properties through their structures not by their components expressing electromagnetic properties that do not occur in nature materials, these structures called negative permittivity and permeability materials or Meta-materials (MMs). Because of non-traditional properties of these materials, they can dramatically add a degree of freedom to the control of electromagnetic waves and have been used in many applications in the field of optical and microwaves. this work explain the most important properties of Metamaterials. On the other hand, it uses fractal distribution in designing a new Metamaterial structure will be applying on whole substrate not only on unitcell and studying their effect on transmission and reflection parameters, and make sure the results by effective material properties extraction. برز في السنوات الأخيرة اهتمام متزايد بنتائج الأبحاث المتعلقة بتفاعل الأمواج الكهرومغناطيسية مع تراكيب مصنعة تعطي سماحية كهربائية (Ɛ) ونفاذية مغناطيسية (µ) سالبين, أي أنها تكتسب خصائصها الكهرومغناطيسية من خلال تركيبها وليس من خلال المواد المكونة لها مبدية خصائص كهرومغناطيسية لا تعطيها المواد الموجودة في الطبيعة وتدعى هذه التراكيب بالمواد سالبة السماحية الكهربائية والنفاذية المغناطيسية Meta-Materials (MMs). وبسبب الخصائص غير التقليدية لهذه المواد, فقد قدمت درجة كبيرة من الحرية في التحكم بالأمواج الكهرومغناطيسية وتم استخدامها في العديد من التطبيقات في مجال الامواج المكروية والضوئية. يلقي هذا العمل الضوء على مواد MMs ويشرح أهم خصائصها, ومن جهة أخرى يستخدم التوزع التجزيئي في تصميم بنية جديدة لمواد Metamaterial سوف يتم تطبيقه على الشريحة ككل وليس على الوحدة الأساس فقط ودراسة تأثير هذا التوزع على معاملات الارسال والانعكاس، و التأكد من النتائج باستخراج خصائص المادة الفعالة.